Ease vs. Noise: On the Conflicting Effects of Transportation Infrastructure - Gabriel Ahlfeldt; Volker Nitsch; Nicolai Wendland (Center for Economic Studies and ifo Institute (CESifo), 2016)
Many transport technologies cause a gnot ]in ]my ]backyard h (NIMBY) reaction of locals in that they often oppose the nearby location of necessary infrastructure despite benefiting from greater mobility. We employ quasi ]experimental research methods to disentangle the offsetting noise and accessibility effects of one technology of mass transit, metro rail, analyzing land price effects of the opening of the first German electrified metro rail line in Berlin in 1902. Examining a long ]run micro ]geographic data set, we find that, ceteris paribus, a 1 km reduction in distance from the nearest station increases land prices (house prices) by 21% (5%), while a 10 db increase in noise depreciates land prices (house prices) by 5% (1%). We show that these effects are underestimated by 40% (access) to 80% (noise) if they are not estimated conditional on each other. A complementary analysis of recent property transactions data suggests that preferences for accessibility have remained quite stable over the 20th century, while noise sensitivity increased substantially. The case for constructing underground as opposed to elevated rail lines is therefore stronger today than a century ago.
Keywords: R12; R14; R41; N73; N74; 330; accessibility; noise; land price; difference-in-differences; regression discontinuity